Kv4 channel blockade reduces motor and neuropsychiatric symptoms in rodent models of Parkinson's disease. Issue 1 (February 2015) - Aidi-knani, Sabrine; Regaya, Imed; Amalric, Marianne; Mourre, Christiane
Abstract : The striatum, a major input structure of basal ganglia, integrates glutamatergic cortical and thalamic inputs to control psychomotor behaviors. Nigrostriatal dopamine (DA) neurodegeneration in Parkinson's disease causes a loss of spinal and glutamatergic synapses in the striatal medium spiny neurons (MSNs). Adaptive responses, a form of homeostatic plasticity, to these changes are caused by a decrease in a potassium Kv4 channel-dependent inactivating A-type potassium (KIA ) current that increases the intrinsic excitability of MSNs. Nevertheless, the functional outcome of these compensatory mechanisms does not allow adequate behavioral recovery in vivo . We thus addressed the question of whether further blockade of Kv4 activity could enhance the striatal responsiveness of MSNs to DA depletion and restore normal function in vivo . To test this hypothesis, we examined the effects of a selective blocker of Kv4 channels, AmmTX3, on the motor, cognitive, and emotional symptoms produced by 6-hydroxydopamine lesions of the nigrostriatal DA pathway in rats. Striatal infusion of AmmTX3 (0.2–0.4 μg) reduced motor deficits, decreased anxiety, and restored short-term social and spatial memories. These results underlie the importance of Kv4 channels as players in the homeostatic responses, and, more importantly, provide a potential target for adjunctive therapies for Parkinson's disease.